Curcumin Oxidation Is Required for Inhibition of Helicobacter pylori Growth, Translocation and Phosphorylation of Cag A - Ray, Ashwini Kumar; Luis, Paula B.; Mishra, Surabhi Kirti; Barry, Daniel P.; Asim, Mohammad; Pandey, Achyut; Chaturvedi, Maya; Gupta, Jyoti; Gupta, Shilpi; Mahant, Shweta; Das, Rajashree; Kumar, Pramod; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Curcumin is a potential natural remedy for preventing Helicobacter pylori-associated gastric inflammation and cancer. Here, we analyzed the effect of a phospholipid formulation of curcumin on H. pylori growth, translocation and phosphorylation of the virulence factor CagA and host protein kinase Src in vitro and in an in vivo mouse model of H. pylori infection. Growth of H. pylori was inhibited dose-dependently by curcumin in vitro. H. pylori was unable to metabolically reduce curcumin, whereas two enterobacteria, E. coli and Citrobacter rodentium, which efficiently reduced curcumin to the tetra- and hexahydro metabolites, evaded growth inhibition. Oxidative metabolism of curcumin was required for the growth inhibition of H. pylori and the translocation and phosphorylation of CagA and cSrc, since acetal- and diacetal-curcumin that do not undergo oxidative transformation were ineffective. Curcumin attenuated mRNA expression of the H. pylori virulence genes cagE and cagF in a dose-dependent manner and inhibited translocation and phosphorylation of CagA in gastric epithelial cells. H. pylori strains isolated from dietary curcumin-treated mice showed attenuated ability to induce cSrc phosphorylation and the mRNA expression of the gene encoding for IL-8, suggesting long-lasting effects of curcumin on the virulence of H. pylori. Our work provides mechanistic evidence that encourages testing of curcumin as a dietary approach to inhibit the virulence of CagA.